2004
DOI: 10.1002/sia.1749
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of self‐assembly of a range of monofunctional aliphatic molecules on magnetron‐sputtered aluminium

Abstract: The adsorption of a range of organic molecules from toluene onto the oxidized surface of magnetronsputtered aluminium metal is studied using sessile drop water contact angle measurements. Molecules with different head group functionalities and various chain lengths are considered, including alkyl carboxylic acids, alkyl phosphonic acids, alkyl amines, alkyl trimethoxysilanes, alkyl trichlorosilanes and epoxy alkanes. Alkyl phosphonic and carboxylic acids are identified as readily forming the most wellpacked mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 22 publications
5
95
1
1
Order By: Relevance
“…normally achieved for systems that have a strong tendency to self-assemble. 31 The water contact angle measured upon removal from solution is presented against the logarithm of pre-assembly ambient storage time in Fig. 1 for toluene, hexadecane and ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…normally achieved for systems that have a strong tendency to self-assemble. 31 The water contact angle measured upon removal from solution is presented against the logarithm of pre-assembly ambient storage time in Fig. 1 for toluene, hexadecane and ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…4 -6,9,27 -32 Most studies aim to attain a constant surface chemistry by using a constant atmospheric exposure time or a cleaning step prior to assembly. 31,33 However, Allara and Nuzzo reported that an acetic acid pretreatment was necessary to obtain consistent close-packed monolayers of alkyl carboxylic acids from dilute hexadecane solutions on aluminium. 29,30 This step was considered to be a reversible chemical passivation process to counter the highly adsorbant nature of the clean native oxide surface.…”
mentioning
confidence: 97%
“…To enhance such charge transfers in an OLED device, thereby improving turn-on voltage, brightness, and external quantum efficiency, coating of triarylamine-based molecules with trichlorosilane-binding groups on ITO as nanoscale layers were performed in the literature [21][22][23]. But, it is a very well-known fact that such kind of silane derivatives and trialkoxy silanes as well have a tendency to self-condensation in solution [24,25] causing the formation of uniform monolayers difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Most likely, the octadecylphosphonic acid molecules are attached to the surface in a bidentate fashion (free P-OH groups). Aluminium oxide, on the other hand, seems to be a less suitable substrate when compared with titania or zirconia, due to the formation of bulk (aluminoalkyl) phosphonate in some cases ( Figure 9) The adsorption of alkylphosphonic and alkanecarboxilic acids and aliphatic triethoxysilanes, trichlorosilanes, amines and epoxides on the surface of magnetron-sputtered aluminium was also studied [182]. Prior to modification the aluminium surface was exposed to air for a short time, which resulted in the formation of a thin oxide layer.…”
Section: Chaptermentioning
confidence: 99%